Creating business values based on spirituality and authenticity of Sustainable Development Goals (SDGs): Inspiration from PwC and BTS - Soeherman, Bonnie; Elim, Valentina (Universitas Hayam Wuruk Perbanas, 2023)
Various issues regarding human rights violations, exploitation of nature, poverty, war, disease, and other sustainability problems have triggered the birth of the Sustainable Development Goals (SDGs) targeting seventeen interlinked objectives by 2030. The implication of this movement, initiated by the United Nations, is a challenge for all organizations and communities to take responsibility for sustainability reporting. There have been many studies and research forums related to reporting, such as Global Reporting Initiative (GRI) and Integrated Reporting (IR). Despite all the progress that has been made by the world community for the success of the SDGs, there is still one fundamental point that has not been widely researched: spirituality. This study believes that without good spirituality, no business entity can carry out programs that are aligned with the SDGs effectively and honestly. This study views this as a gap that needs to be studied more deeply in terms of spirituality and the authenticity of the SDGs. By adopting two case studies,